Falls, non-accidental falls and syncope in community-dwelling adults aged 50 years and older: Implications for cardiovascular assessment - Kenny, Rose (My University, 2017)
Objectives: To calculate the prevalence of all falls, non-accidental falls and syncope in an older population and characterize cardiovascular risk profiles. Design: Prospective, longitudinal cohort study. Setting: The first two waves of data from the Irish Longitudinal Study on Ageing (TILDA). Participants: 8172 community-dwelling adults aged 50 years and older resident in the Republic of Ireland Measurements: Self-reported history of all falls, non-accidental falls and syncope in the year preceding the first two waves of data collection. Demographic factors and self-reported cardiovascular conditions were used to characterize cardiovascular risk profiles. Results: The prevalence of all falls in the past year was 19.2% or 192 per thousand persons and increased with age (50–64 years 17.5%; 65–74 years 19.4%; 75+ years 24.4%). Non-accidental falls had an estimated prevalence of 5.1% or 51 falls per thousand persons and accounted for 26.5% of all falls reported and also increased with age (50–64 years 4.0%; 65–74 years 5.5%; 75+ years 8.0%). The prevalence for syncope was estimated to be 4.4% or 44per thousand persons but did not show a similar age gradient. Participants with at least 5 cardiovascular conditions were more likely to report all falls (OR = 2.07, 95% CI 1.18–3.64, p<0.05) and NAF (OR = 2.89, 95%CI 1.28–6.52, p<0.05). Conclusions: The prevalence of all falls and non-accidental falls increases with age but the same pattern was not consistently observed for syncope. There is an increased odds of reporting all three outcomes with increasing number of self-reported cardiovascular conditions. Further work is needed to uncover the interplay between cardiovascular disease and subsequent falls.
PUBLISHED
cited By 0
Keywords: Falls; Ageing; Cardiovascular risk; Ageing